2009
DOI: 10.2174/1874230000903010017
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia in the Shadow of Chronic Social Defeat Stress, or when the Experimental Context Matters

Abstract: One of the core symptoms of major depression in human is anhedonia. For that reason, one of the main requirements towards experimental depression models is that they be able to demonstrate anhedonia in animals, that have been exposed to stressful events, and other behavioral changes attributable to a depression-like state. However, the results presented in the literature are contradictory: sweet solution intake, which is considered as a parameter of hedonic/anhedonic behavior in animals, responds quite differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Notably, the changes in adolescent behaviors under chronic SDS are similar to those in adult males in similar experimental paradigms. In adult mice, long SDS dramatically increases anxiety and depressiveness, decreases sucrose consumption [ 35 ] , [36] , [ 37 ] , disturbs social communications, and increases repetitive behaviors [ 38 ] . However, there are also important distinctions in the response of adults and adolescents to SDS: while in adult males depressiveness was shown to develop after 21 days of SDS in our experimental paradigm [ 35 ] , in SDS adolescents a depressive-like state develops faster, appearing after 14 days in the Porsolt test as longer periods of passive behavior ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the changes in adolescent behaviors under chronic SDS are similar to those in adult males in similar experimental paradigms. In adult mice, long SDS dramatically increases anxiety and depressiveness, decreases sucrose consumption [ 35 ] , [36] , [ 37 ] , disturbs social communications, and increases repetitive behaviors [ 38 ] . However, there are also important distinctions in the response of adults and adolescents to SDS: while in adult males depressiveness was shown to develop after 21 days of SDS in our experimental paradigm [ 35 ] , in SDS adolescents a depressive-like state develops faster, appearing after 14 days in the Porsolt test as longer periods of passive behavior ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Male mice exhibiting repeated aggression in daily agonistic interactions enter a pathological psychotic-like state characterized, e.g., by symptoms of increased aggressiveness, hyperactivity, stereotypical behavior, and disturbances in social recognition (reviewed in [20,21]). Mice with chronic social defeat experience develop a mixed anxiety/depression-like state with symptoms of hypoactivity, behavioral deficits, anhedonia, and other problems [22][23][24][25][26]. We have previously demonstrated that, in the MRNs of both groups of animals with the opposite social experiences, there is underexpression of several key genes responsible for the synthesis, transport, and binding of serotonin [27][28][29].…”
Section: Introductionmentioning
confidence: 99%